A Preliminary Discussion on the Treatment of Emotional Disorders in Traditional Chinese Medicine - Zhang, Jiali; Song, Qilao (Journal of Contemporary Medical Practice, 2024)
In recent years, with the development of the bio-psycho-social medical model, more and more attention has been paid to the relationship between mental and emotional factors and the Five zang organs. Emotional disorders is a series of related diseases caused by the dysfunction of the five zang organs of the human body caused by the seven emotions too much, and the harm to the human body should not be underestimated. When treating diseases, we should start from two aspects: medication and emotional regulation.